Alum-Catalyzed Synthesis of 3-(1H-Pyrrol-2-yl)-2H-chromen-2-ones: A Water–PEG 400 Binary Solvent Mediated, One-Pot, Three-Component Protocol - Pal, Gargi; Paul, Sanjay; Das, Asish R. (Synthesis, 2013)
A novel, one-pot, three-component condensation reaction of 3-(bromoacetyl)coumarin, acetylacetone, and an amine using the inexpensive, environmentally benign, and mild catalyst alum as an efficient catalyst and the water–PEG 400 binary solvent system gives 3-(1-aryl-4-acetyl-5-methyl-1H-pyrrol-2-yl)-2H-chromen-2-ones, a new heterocyclic scaffold containing both the coumarin and pyrrole nuclei in a single molecule, in good to excellent yields. This methodology offers several advantages: simple procedure, excellent yields, short reaction times, and green aspects such as avoiding toxic catalysts and solvents.
Keywords: pyrrole derivatives; coumarin; alum; binary solvent; green protocol